A Patient Presenting with Bilateral Lung Lesions, Pleural Effusion, and Proteinuria. (9th May 2013) - Samara, Katerina D.; Papadogiannis, Giorgos; Nicholson, Andrew G.; Magkanas, Eleutherios; Stylianou, Konstantinos; Siafakas, Nikolaos; Antoniou, Katerina M.
Abstract : Diagnosis and management of a systemic vasculitis are among the most demanding challenges in clinical medicine. A patient with a past history of cryptogenic organizing pneumonia presents with new bilateral lung lesions, unilateral pleural effusion, and significant proteinuria. The patient tested p-ANCA and anti-MPO positive but c-ANCA negative. A diagnosis of granulomatosis with polyangiitis GPA was reached after performing both renal and lung biopsies. Step-by-step differential diagnosis and management are discussed.